Occurrence of PM2.5 and PM0.1 at high polluting event days in Ha Noi and health implication - Thi Le Ha, Vo; Bich Thuy, Ly; Dieu Anh, Van; Thi Thu Hien, Nguyen; Duy Nam, Dao; Trung Dung, Nghiem; Quoc Dat, Nguyen (Vietnam Journal of Science and Technology, 2024)
High levels of fine (PM2.5) and ultrafine (PM0.1) particles in the atmosphere can cause adverse effects on the environment and human health. This study aims at determining the mass concentrations of PM and health risks on pollution event days (episodes) in Hanoi. Semi-daily samples (daytime and night-time) of PM2.5 and PM0.1 were collected at Hanoi University of Science and Technology, in December 2021. The daily PM2.5 concentrations were in the range of 39 – 204 µg/m3 (average of 119 µg/m3). Those of PM0.1 varied from 11 to 30 µg/m3 (average of 22 µg/m3). There is negligible change on daytime and night-time PM0.1 concentrations, whereas those levels of PM2.5 were remarkably different. PM2.5 daytime concentrations were in the range of 39 – 205 µg/m3 with an average of 106 µg/m3. The level ranges of night-time were slightly wider which varied from 39 to 230 µg/m3 (average of 136 µg/m3). A prolonged episode of PM2.5 (which is defined by the criterion of PM2.5 > 50 µg/m3) was found with an intensity of 26 days in December. During the pollution episode, the Monte Carlo simulation showed that respirable doses were the highest for the adult (above 21 years) for chronic effects, whereas the highest doses for acute were observed in the children (0-3 years), which has implications in the adverse health effects for sensitive groups. The sensitive analysis finds the concentration of PM to be the most influencing factor in inhalation dose estimation.